The unknown shown by numerical tools: application to right dysfunction. (8th February 2021) - Comunale, G; Castaldi, B; Peruzzo, P; Razzolini, R; Padalino, M; Di Salvo, G; Susin, FM
Abstract: Funding Acknowledgements: Type of funding sources: Public Institution(s). Main funding source(s): Ph.D. Research Grant Introduction. Numerical modelling of cardiovascular flows is emerging as a powerful tool when applied to clinical practice, thanks to its capability of describing hemodynamics non-invasively. Among the different approaches, lumped parameters (0D) models present the advantage of describing the complete circulation at low computational cost, with strong stress on cause-effect relationships between the different functional elements and flow/pressure waveforms. 0D models fully express their potentiality when applied to complex physio-pathological conditions. This work applies such an approach to the right ventricular (RV) dysfunction, modelling the case of an equal systolic and diastolic percentage dysfunction, i.e., 60%. The model highlights how the right dysfunction affects the left performances, despite the unaltered left ventricular (LV) functionality. Purpose. Numerical tools may help clinicians in understanding the characteristic features of physio-pathological conditions, clearly differentiating the contributions of single functional elements. Methods. We develop a 0D model of both left and right circulation, in which heart chambers are simulated with the time-varying elastance concept. Ideal diodes associated with resistances are adopted for the heart valves, and the dissipative effects for the vascular beds and elastic properties for the great vessels are considered. The healthy and the RV dysfunction cases are considered, and, for the pathological condition, we impose a 60% right systolic and diastolic dysfunction. Results. Fig. 1 shows an example of the outputs calculated by our model e.g., the pressure-volume (pV) loops which, in the clinical practice, are obtained with invasive measurements. On the right heart, the simulated dysfunction reduces systolic pressures, augments diastolic pressures and causes an enlargement of the ventricle (Fig. 1a). Interestingly, the pathology reflects also on the LV: the left pV loop exhibits a left/downward shift, despite the unaltered functionality (Fig. 1b). Overall hemodynamic variables reported in Fig. 1c confirm that RV dysfunction causes a deterioration of the global hemodynamics, i.e., CVP increases and, SV and CI decrease. Moreover, RV dysfunction reduces not only the RV performances (EFrv), but the well-functioning LV activities (EFlv) as well. These findings strengthen the arising clinical practice of checking the LV performance to understand when it is necessary to intervene, e.g., in the presence of the Tetralogy of Fallot. Conclusion. Numerical models are powerful tools that can help clinicians in understanding the featuring element of a physio-pathological condition. Here, we have shown that RV dysfunction reduces LV functionalities, thus corroborating the emerging idea that optimal timing for intervention in right diseases requires that also the left side circulation is considered.